Hubungan Waktu Tunggu Dengan Tingkat Kepuasan Pasien Rawat Jalan Rumah Sakit Ibnu Sina Yayasan Wakaf Universitas Muslim Indonesia (Window of Public Health Journal, 2025)
Long waiting times among patients are most commonly seen in all health services and play a significant role in various public health problems, including reduced access to health care services, disruption of work patterns in health care centers, and patient dissatisfaction. This study aimed to determine the relationship between waiting times for registration services, drug checks at the polyclinic, and taking prescription and non-prescription drugs at Ibnu Sina Yw-umi Hospital, Makassar City, in 2024. The type of research is a quantitative method with a cross-sectional approach. The population of this study was an average of 6592 outpatients, and a sample of 152 respondents was obtained. The sampling technique was purposive sampling with a survey using a questionnaire. Data were processed using univariate and bivariate analysis and the chi-square statistical test. The results of the study showed that there was a significant relationship between the waiting time for services and the satisfaction of outpatients. The standard p-value used was 0.05, namely in the registration service in the chi-square statistical test with a p Value (p = 0.0001), drug examination at the polyclinic was obtained (p = 0.0113), the time for taking non-prescription drugs (p = 0.0000) and taking prescription drugs (p = 0.0000). From the results above, it can be concluded that there is a significant relationship between the waiting time for registration services, taking non-prescription and prescription drugs, and the satisfaction of outpatients. Meanwhile, the waiting time for doctor's examination services at the polyclinic has no relationship with outpatients' satisfaction.